已知a^2+ab=3,b^2+ab=-2 求a^2+2ab+b^2和a^2-b^2的值.

来源:学生作业帮助网 编辑:作业帮 时间:2024/09/09 10:25:38
已知a^2+ab=3,b^2+ab=-2 求a^2+2ab+b^2和a^2-b^2的值.
x){}K㌴lu ]#g@FI@z<] {l׬_`gCH lul llMm 6ـ9bE6&m,[QQ Tk^D"~ODN⭂nIYf/^Ov';<|]  4 j;

已知a^2+ab=3,b^2+ab=-2 求a^2+2ab+b^2和a^2-b^2的值.
已知a^2+ab=3,b^2+ab=-2 求a^2+2ab+b^2和a^2-b^2的值.

已知a^2+ab=3,b^2+ab=-2 求a^2+2ab+b^2和a^2-b^2的值.
a^2+2ab+b^2=3-2=1 a^2-b^2=3+2=5

1,
5

a^2+2ab+b^2=a^2+ab+b^2+ab=3-2=1
a^2-b^2=(a^2+ab)-(b^2+ab)=3-(-2)=5

a^2+ab=3,b^2+ab=-2所以a^2+2ab+b^2=a^2+ab+b^2+ab=1
a^2-b^2=a^2+ab-(b^2+ab)=5

a^2+ab=3,b^2+ab=-2
a^2+ab+b^2+ab=1
所以a^2+2ab+b^2=1
(a^2+ab) - (b^2+ab)=5
所以a^2-b^2=5

因为a^2+ab=3,b^2+ab=-2
两式相加得a^2+2ab+b^2=1
a^2-b^2=a^2+ab-(b^2+ab)=3-(-2)=5